Peficitinib inhibits fibroblast-like synoviocyte activation and angiogenic vascular endothelial tube formation via inhibitory effects on PDGF and VEGF signaling in addition to JAK - Go Ishikawa; Chulwon Kwon; Yasutomo Fujii (Elsevier, 2022)
Purpose: Peficitinib and tofacitinib are known to suppress inflammation in rheumatoid arthritis (RA) by inhibiting Janus kinases (JAKs). However, these effects on tyrosine kinases other than JAKs have not yet been well investigated. We evaluated the effects of peficitinib and tofacitinib on platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF) receptor tyrosine kinases (RTKs) and on the activation of fibroblast-like synoviocytes (FLSs) and endothelial cells, main pathological causes of RA. Methods: Peficitinib and tofacitinib were tested in PDGF and VEGF RTK assays. We then used FLSs derived from RA patient (RA-FLSs) and human umbilical vein endothelial cells (HUVECs) to study the effects of peficitinib and tofacitinib on PDGF- and VEGF-induced signal transduction and on the activation of RA-FLSs and endothelial cell tube formation. Findings: Peficitinib, not tofacitinib, inhibited both PDGF and VEGF RTKs in addition to JAKs in cell-free assay system. Peficitinib and tofacitinib attenuated PDGF- and VEGF-induced intracellular signal transduction pathways in RA-FLSs and HUVECs to varying degrees. Only peficitinib potently inhibited PDGF-induced secretion of interleukin-6, VEGF, and matrix metalloproteinase-3 in RA-FLSs, and endothelial cell tube formation by HUVECs. Conclusion: Peficitinib may improve RA through inhibition of PDGF and VEGF signal transduction, in addition to JAK inhibition.